Dampak Sosial Ekonomi Pengelolaan Ekowisata Mangrove Kampoeng Kepiting Terhadap Nelayan Desa Tuban Kabupaten Badung - Wardani, I Gusti Made Intan Sanisca; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2018)
Tourism in each region should be able to provide benefits to the local community, especially the economic benefits. Sustainable tourism, should be intensified in tourism development at this time, because they have a positive impact on society, but it does not negatively impact the natural state. This research was conducted in Ekowisata Mangrove Kampoeng Kepiting , Tuban Village, Badung Regency. This study used a technique-depth interviews with the head of the fishermen, and the secretary of the fishermen, and using purposive sampling method. This research was conducted with a qualitative descriptive analysis techniques that will be used to describe the results of interviews that have been conducted. The results of this study, that Ecotourism is managed entirely by a group of fishermen, with the division of tasks to handle all existing activities. Socio-economic impact that occurs by adding the income of fishermen, full employment, building a fishermen economy, changing the mindset of fishermen on the environment, fishermen have the skills, able to organize, and interact well. From the results of this study are expected to be fishermen, to increase the fishing economy, and maintaining the principles which will not be affected to investors, both domestic investors and foreign investors, because the people who should be able to host their own country.   Keywords : ecotourism, management, socio-economic impacts